Liver Transplantation for Hereditary Transthyretin Amyloidosis. Issue 9 (September 2015) - Ericzon, Bo-Göran; Wilczek, Henryk E.; Larsson, Marie; Wijayatunga, Priyantha; Stangou, Arie; Pena, João Rodrigues; Furtado, Emanuel; Barroso, Eduardo; Daniel, Jorge; Samuel, Didier; Adam, Rene; Karam, Vincent; et al.
<x xml:space="preserve">Abstract</x> Background Until recently, liver transplantation (Ltx) was the only available treatment for hereditary transthyretin (TTR) amyloidosis; today, however, several pharmacotherapies are tested. Herein, we present survival data from the largest available database on transplanted hereditary TTR patients to serve as a base for comparison. Methods Liver transplantation was evaluated in a 20-year retrospective analysis of the Familial Amyloidosis Polyneuropathy World Transplant Registry. Results From April 1990 until December 2010, data were accumulated from 77 liver transplant centers. The Registry contains 1940 patients, and 1379 are alive. Eighty-eight Ltx were performed in combination with a heart and/or kidney transplantation. Overall, 20-year survival after Ltx was 55.3%. Multivariate analysis revealed modified body mass index, early onset of disease (<50 years of age), disease duration before Ltx, and TTR Val30Met versus non-TTR Val30Met mutations as independent significant survival factors. Early-onset patients had an expected mortality rate of 38% that of the late-onset group (P < 0.001). Furthermore, Val30Met patients had an expected mortality rate of 61% that of non-TTR Val30Met patients (P < 0.001). With each year of duration of disease before Ltx, expected mortality increased by 11% (P < 0.001). With each 100-unit increase in modified body mass index at Ltx, the expected mortality decreased to 89% of the expected mortality (P < 0.001). Cardiovascular death was markedly more common than that observed in patients undergoing Ltx for end-stage liver disease. Conclusions Long-term survival after Ltx, especially for early-onset TTR Val30Met patients, is excellent. The risk of delaying Ltx by testing alternative treatments, especially in early-onset TTR Val30Met patients, requires consideration.